Temperature dependence of photoinduced birefringence in polystyrene doped with Disperse Red-1 - Dall'Agnol, Fernando; Silva, Josmary R.; Zílio, Sérgio C.; Oliveira Jr., Osvaldo N.; Giacometti, José A. [UNESP] (My University, 2002)
A theoretical model on the basis of the free-volume concept is presented explaining the temperature dependence of photoinduced birefringence in polystyrene films that contain Disperse Red-1. Birefringence increases with temperature up to 180 K as the free volume for isomerization increases, and then decreases as thermally activated processes dominate. The fast process of birefringence decay has a time constant that increases with temperature at low temperatures, due to the change in photoisomerization.
Keywords: Disperse Red-1; Free volume; Isomer/isomerization; Photoinduced birefringence; Polystyrene